Kepuasan konsumen sebagai moderasi kenaikan PPN dan celebrity endorser terhadap minat beli - Ayem, Sri; Wahidah, Umi; Nurlitawati, Merna; Kasim, Ahmad Nizam Che (Entrepreneurship Bisnis Manajemen Akuntansi (E-BISMA), 2025)
Technological advances and changes in tax regulations, competition in the business sector present various possibilities and difficulties for business people who want to increase consumer interest in their products. With consumer satisfaction as a moderator variable, the purpose of this study is to determine whether celebrity endorsers and VAT increases affect purchase intention. This study collected data using purposive techniques and a quantitative approach using a questionnaire involving 100 respondents who are users of skin care products and have seen promotional advertisements for skin care products on social media in the Special Region of Yogyakarta. Data were analyzed using Structural Equation Modeling (SEM) techniques with AMOS software. The results showed that celebrity endorsers and VAT increases have a positive effect on consumer interest, which shows that these two strategies can increase consumer interest in making purchases. The results also reveal that the moderating variable of customer satisfaction can moderate the relationship between the increase in VAT and celebrity endorsers on purchase intention. This shows that an increase in VAT and celebrity endorsers can increase consumer buying interest, so both can be used as effective marketing strategies. In addition, customer satisfaction plays an important role as a moderator that strengthens the influence of these two factors on purchase intention.